(untitled) (LACCEI, 2024)
The work had the objective of analyzing the ultraviolet index values in the Puno region, for which it is considered a reference point in the thirteen provinces. To obtain ultraviolet index values, data from the weather station of the city of Puno for the period 2016-2021 is considered to obtain a correction equation for the data obtained from the Giovanni NASA website and thus obtain maximum daily values for the region. from Puno. Consider a theoretical model to obtain the ultraviolet index which is for clear sky conditions. The evaluation statistics used are the standard error and the linear correlation coefficient between the estimated data and values measured by the weather station. It has been concluded that it was possible to obtain ultraviolet index values for the Puno region with a reliability of 95% and an error of 0.80 for the city of Puno, obtaining very high and extremely ultraviolet index values for summer times.